Hubungan Aktivitas Fisik Dengan Tingkat Kebugaran Jasmani Peserta Didik - Saharani, Vivi Widya; Arief, Nur Ahmad (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The research was conducted to analyze the relationship and contribution of physical activity to the physical fitness level of 10th-grade students at SMA Negeri 3 Mojokerto. The design applied was a correlational study with a quantitative model. The Physical Activity Questionnaire-Adolescents (PAQ-A) was the instrument used to assess physical activity, and the Test of Physical Fitness for Students of Nusantara (TKPN) was the instrument used to assess physical fitness. The subjects were selected using a simple random sampling technique and calculated utilizing the Slovin formula to determine the total subjects. Based on the Slovin formula calculation, the subjects used amounted to 155 students class X of SMA Negeri 3 Mojokerto. The investigation used Spearman Rank Correlation data analysis to test the correlation between the two variables. The findings showed the significance value of the correlation between physical activity and physical fitness level was 0.000 < 0.05. The correlation coefficient between the two variables was 0.307 (positive direction), meaning that the better the physical activity, the higher the physical fitness level of the students. Based on the correlation coefficient value (r) of 0.307, it was interpreted according to the correlation coefficient guidelines as indicating a moderate level of relationship.